Health adverse effects of formaldehyde exposure to students and staff in gross anatomy (International Journal of Scientific Research and Management (IJSRM), 2018)
Formaldehyde is an anxious gas used as a tissue preservative of cadavers in anatomy halls. Therefore, laboratory staff and students are at high risk of different clinical complications due to the continuous exposure to formaldehyde. The present questionnaire-based study evaluates the effects of formaldehyde exposure on veterinary students and staff in the anatomy gross dissection laboratory, University of Tripoli, Libya. A total of 104 students and 6 anatomy staff members completed a questionnaire of 24 questions related to the clinical symptoms observed after formaldehyde exposure and the answers were assessed using a six point (0-5) scale. Students had a high prevalence of nasal itching 78(75%), eyes burning 78(75%), excessive lacrimation 76(73%), eyes redness 60(58%), headache 64(62%) and respiratory distress 61(59%). Smoking and wearing glasses or gloves worsened many symptoms while wearing masks minimized other symptoms and male students were more affected than females. All anatomy staff members (100%) reported nasal itching, burning and congestion, eyes burning and redness, excessive lacrimation, cough and respiratory distress and less than that (83%) suffered from mouth dryness, headache, temporary loss of their ability to recognize the smell of formaldehyde and needed a physician assistance after the exposure to formaldehyde. The repeated exposure to formaldehyde in gross anatomy dissection has harmful effects on both students and staff member and finding alternative preservation methods, such as freezing, would be safer than using the formaldehyde